Assessing and comparing nutritional status and related factors among 6-48 months old children born in the damaged rural and urban areas of Varzeghan after the 2012 earthquake - Mokhtari, Rasoul; Ghalichi, Faezeh; Mohammad, Asghari Jafarabadi; Barzegar, Ali (Progress in Nutrition, 2020)
Background: Infants and young children have been identified as the most nutritionally vulnerable group in catastrophic situations such as earthquakes. Malnutrition and poor feeding practices during the early years of life could adversely affect child’s growth, cognitive, physical and social development. Objectives: The objective of this study was to assess and compare nutritional status and related factors among 6-48 months old children born in the damaged rural and urban areas of Varzeghan after the 2012 earthquake. Methods: 250 children between 6-48 months living in Varzeghan and 60 damaged villages participated in this cross-sectional descriptive study. Anthropometric data were gathered and the three indices of malnutrition, wasting (weight/height), underweight (weight/age) and stunting (height/age) were calculated and assessed according to z-score. These data were compared with the documented files gathered in health institutes before the earthquake. Results and Conclusion: There were statistically significant differences in wasting, underweight and stunting before and after the earthquake in different areas. The most prevalent nutritional complications according to z-score